Coexistence of Kondo effect and Weak anti-localization in Topological insulator/Ferromagnetic heterostructure - Ghosh L.; Ghosh S.; Dixit S.; Alam M.; Patel N.; Tiwari A.; Shahi P.; Uwatoko Y.; Chatterjee S. (My University, 2025)
The presence of a magnetic impurity in a topological insulator weakens the time-reversal symmetry by creating a limited gap at the Dirac point, and could result in the creation of new quantum states. On the other hand, causing magnetization in a topological insulator through the interlayer proximity effect to a magnetically ordered system is a better choice, as magnetic doping may have negative effects. In this report, the magnetic and magneto-transport properties of FeSe intercalated Bi2Se3 crystals and FeSe/Bi2Se3/FeSe hetero-structure have been investigated. The XPS depth profile was studied to confirm the layered structure of the hetero-structure. The weak anti-localization state in the multilayer system has been seen to coexist with the Kondo effect, which may have caused by the interfacial magnetic domains modifying the electronic characteristics at interfaces. Such magnetic spin-induced inter-layer coupling can be a pathway to room-temperature spintronic applications. © 2024